A comparative study of multi beam echo sounder and side scan sonar images on shipwrecked - Nur Ain Fadzillah Marzuki, author 642285; Rusli Othman, supervisor 492439; Fakulti Geoinformasi dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Kejuruteraan Geomatik))